Gravity Model by Panel Data Approach: An Empirical Application with Implications for South Asian Countries. (November 2015) - Kumar, Sushil; Ahmed, Shahid
This article has examined the determinants of export and import flows of countries in the South Asia through estimations for a country panel data of eight countries during the period 1985–2011 using a gravity model. The estimated result suggests that gross domestic product (GDP) and population among other factors can explain export and import flows. Perhaps the most important finding of the study is that South Asia Free Trade Agreement (SAFTA) has produced trade creation among its members. Finally, the study found that geographic distance might be impeding trade, and tariff has negative effect on the trade. The study also found that the nature of trade is intra-industry among the member countries of South Asian Association for Regional Cooperation (SAARC).